Study guide for Ralph, Lerner, Meacham, Wood, Hull, and Burns "World civilizations" - Allen, J. Michael, 1956- (W. W. Norton, 1997)
The earliest beginnings. Mesopotamian civilization. Egyptian civilization. The Hebrew and early Greek civilizations. Ancient Indian civilization. Ancient Chinese civilization. Near Eastern empires and ancient India maps. Greek civilization. The Hellenistic civilization. Roman civilization...